Late and Multiple Bidding in Second Price Internet Auctions: Theory and Evidence Concerning Different Rules for Ending an Auction - Axel Ockenfels; Alvin E. Roth (Center for Economic Studies and ifo Institute (CESifo), 2003)
In second price internet auctions with a fixed end time, such as those on eBay, many bidders snipe', i.e., they submit their bids in the closing minutes or seconds of an auction. Late bids of this sort are much less frequent in auctions that are automatically extended if a bid is submitted very late, as in auctions conducted on Amazon. We propose a model of second price internet auctions, in which very late bids have a positive probability of not being successfully submitted, and show that sniping in a fixed deadline auction can occur even at equilibrium in auctions with private values, as well as in auctions with uncertain, dependent values. Sniping in fixed-deadline auctions also arises out of equilibrium, as a best reply to incremental bidding. However, the strategic advantages of sniping are eliminated or severely attenuated in auctions that apply the automatic extension rule. The strategic differences in the auction rules are reflected in the field data. There is more sniping on eBay than on Amazon, and this difference grows with experience. We also study the incidence of multiple bidding, and its relation to late bidding. It appears that one substantial cause of late bidding is as a strategic response to incremental bidding.
Keywords: 330